2020
DOI: 10.3389/fneur.2020.00897
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension Is Associated With Cognitive Decline in Parkinson Disease

Abstract: Introduction: Cognitive impairment and orthostatic hypotension (OH) are common, disabling Parkinson disease (PD) symptoms that are strongly correlated. Whether the relationship is causative or associative remains unknown. OH may occur without classic orthostatic symptoms of cerebral hypoperfusion (i.e., lightheadedness or dizziness). Whether longitudinal differences in cognition occur between symptomatic and asymptomatic OH patients has not been explored. Objectives: We chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…similar association between a reduction in MRI signal in the locus coeruleus and RBD 58 and, in those patients with PD and RBD, this signal reduction is associated with cog nitive deterioration and orthostatic hypotension 59 . Moreover, a reduction in brain noradrenaline trans porter availability correlates with cognitive decline and orthostatic hypotension in PD 59 and neurogenic ortho static hypotension in PD owing to noradrenergic den ervation of the heart is independently associated with cognitive decline 60 . The underlying mechanism of this association is due to cerebral hypoperfusion caused by orthostatic hypotension, which impairs cognitive function, with noradrenalineenhancing drugs recom mended for the treatment of orthostatic hypotension 61,62 .…”
Section: Noradrenergic Locus Coeruleus and Sympathetic Systemsmentioning
confidence: 99%
“…similar association between a reduction in MRI signal in the locus coeruleus and RBD 58 and, in those patients with PD and RBD, this signal reduction is associated with cog nitive deterioration and orthostatic hypotension 59 . Moreover, a reduction in brain noradrenaline trans porter availability correlates with cognitive decline and orthostatic hypotension in PD 59 and neurogenic ortho static hypotension in PD owing to noradrenergic den ervation of the heart is independently associated with cognitive decline 60 . The underlying mechanism of this association is due to cerebral hypoperfusion caused by orthostatic hypotension, which impairs cognitive function, with noradrenalineenhancing drugs recom mended for the treatment of orthostatic hypotension 61,62 .…”
Section: Noradrenergic Locus Coeruleus and Sympathetic Systemsmentioning
confidence: 99%
“…Lower Montreal Cognitive Assessment (MoCA) scores and worse decline during follow-up period were observed among PD-OH group. Presence of OH symptoms did not influence cognitive deterioration [68].…”
Section: Orthostatic Hypotensionmentioning
confidence: 83%
“…The impairment is more severe when SH is combined with OH [2]. However, a few studies did not confirm this observation [68,69,73].…”
Section: Supine Hypertensionmentioning
confidence: 95%
“…A secondary prediction was that LC volume would positively correlate with cognitive scores. Finally, recent work has found that PD-related OH, independent of OHSx, confers risk of cognitive decline (39). Some have proposed that OHSx may rely on function of adrenergic output by the LC (40).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cognitive impairment, also a risk for quality of life reduction, is common in early PD (15-20% in de novo PD), with upwards of 80% of MCI-PD patients progressing to dementia (8-10). Interestingly, several studies have found those with OH, irrespective of OHSx, have a greater risk of cognitive impairment (11)(12)(13)(14). Neuropathologic mechanisms underlying this link remain unclear.…”
Section: Introductionmentioning
confidence: 99%